Applied mycology and biotechnology - Khachatourians, George G., 1940-; Arora, Dilip K.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2001)
This volume of Applied Mycology and Biotechnology completes the set of two volumes dedicated to the coverage of recent developments on the theme "Agriculture and Food Production". The first volume provided overview on fungal physiology, metabolism, genetics and biotechnology and highlighted their connection with particular applications to food production. The second volume examines various specific applications of mycology and fungal biotechnology to food production and processing. In the second volume coverage on two remaining areas of the theme, food crop production and applications in the foods and beverages sector, is presented. The interdisciplinary and complex nature of the subject area, combined with the need to consider the sustainability of agri-food practices, its economics and industrial perspectives, requires a certain focus and selectivity of subjects. In this context the recent literature contained in this work will help readers arrive at comprehensive, in depth information on the role of fungi in agricultural food and feed technology. As a professional reference this book is targeted towards agri-food producer research establishments, government and academic units. Teachers and students, both in undergraduate and graduate studies, in departments of food science, food technology, food engineering, microbiology, applied molecular genetics and biotechnology will also find this work useful.
v. 1. Agriculture and food production -- v. 2. Agriculture and food production -- v. 3. Fungal genomics.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Fungi -- Biotechnology; Agricultural biotechnology; Food -- Biotechnology; Champignons -- Biotechnologie; Biotechnologie agricole; Aliments -- Biotechnologie; Agricultural biotechnology; Food -- Biotechnology; Fungi -- Biotechnology; Electronic books